2013
DOI: 10.5812/hepatmon.7048
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced Anti-HBs Level in 5-6 Year-Old Malnourished Children

Abstract: Background: Malnutrition is the most common cause of immune deficiency. It results in reduced secretion of T-cells and B-cell-stimulating factors leading to declining of special immunoglobulins. On the other hand, hepatitis B, as a major world health problem, can be prevented effectively by vaccination. Three doses of hepatitis B virus (HBV) vaccine induce protective levels of anti-hepatitis B surface (anti-HBs) in 95% of healthy children. This level decreases gradually over time. Objectives: The goal of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…For instance, Rey et al (41) found that nutritional status was significantly associated with response to HBV vaccination in Senegal and Cameroon, where 85% of children with normal nutritional status were protected (anti-HBs ≥10 IU/L) versus 60% with moderate to severe malnutrition. In Iran, Karimi et al (42) found a significant decrease in the immune response to HBV vaccine in malnourished children (60.2%) and that severe acute malnutrition produced a higher protective immune response than moderate acute malnutrition. Losonsky et al (43) concluded that low and poor weight gains in the first 6 months of life were associated with reduced immunogenicity (71%) following three doses of HBV vaccine in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Rey et al (41) found that nutritional status was significantly associated with response to HBV vaccination in Senegal and Cameroon, where 85% of children with normal nutritional status were protected (anti-HBs ≥10 IU/L) versus 60% with moderate to severe malnutrition. In Iran, Karimi et al (42) found a significant decrease in the immune response to HBV vaccine in malnourished children (60.2%) and that severe acute malnutrition produced a higher protective immune response than moderate acute malnutrition. Losonsky et al (43) concluded that low and poor weight gains in the first 6 months of life were associated with reduced immunogenicity (71%) following three doses of HBV vaccine in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Viral hepatitis B is one of the most serious public health problems worldwide ( 1 ). There are more than two billion people infected in the world, of whom about 400 million are chronic carriers ( 2 ) and approximately 1 million people die annually because of the disease ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination represents the main instrument to prevent HBV infection ( 1 , 13). Immunization should be carried out in three doses, with a month interval between the first and second dose and of six months between the first and the third dose, in order to stimulate the production of antibodies anti-HBs ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…el-Gamal Y et al 18reported that seroconvertion rate was lower in children with protein calorie malnutrition than healthy children (87% vs 100%, respectively). In contrast with these reports, Karimi et al (19) and Karaoglu et al(13) reported that severity of malnutrition does not affect vaccine-induced antibody level and seroprotection rate. No correlation was found between response rate and mid-upper arm circumference, but anti-HBsAg titers were significantly lower in children who had lower mid-upper arm circumference.…”
Section: Discussionmentioning
confidence: 80%